Efeito das mudanças posturais passivas sobre a motilidade gastrintestinal em ratos acordados - Silva, Camila Meirelles de Souza (2014)
Cardiovascular disorders such as heart failure and acute coronary syndrome cause gastrointestinal disorders with frequency, suggesting the intervention of cardiovascular physiology in the gastrointestinal tract (GIT). Acute variations in blood volume change motor behavior of GIT, however, interventions used to investigate this phenomenon involve invasive procedures. Thus, postural changes resulting from passive tilt testing emerge as a noninvasive tool to promote spontaneous redistribution of blood volume and the analysis of the physiological role of this phenomenon. For such rats were anesthetized, endowing them with catheters and performing gastrostomy for obtaining hemodynamic monitoring and analysis of gastrointestinal motility. On the eighth day after surgery, the rats was submitted for 75 min to continuous monitoring of Mean Arterial Pressure (MAP, mmHg), Heart Rate (HR, b.p.m.), Central Venous Pressure (CVP, mmHg) and Cardiac Output (CO, mL / min). After the initial 30 minutes monitoring (baseline period), the rats were fed the test meal (phenol red 0.75 mg / ml and 5% glucose) via gastric tube. Then underwent sudden postural change: Group tilt up (+75 °) or tilt down group (-75 °), or kept in a horizontal position (control group). After 10, 20 or 30 min, animals were euthanized for evaluation of the fractional recovery of the dye in the stomach. Then we evaluated the intestinal transit by infusion of test meal via gastric tube directly into the small intestine 10 min postprandial. Manometry were performed via the evaluation of gastric contractions by a balloon inserted into the stomach to determine the frequency and amplitude of gastric contractions and motility index. The tilt up (+ 75 °) increased (P <0.05) the MAP, HR and the CO. CVP showed a biphasic response (P<0.05). In the context of gastrointestinal motor behavior, the tilt-up accelerated (P<0.05) the gastric emptying of liquid and shifted baseline manometry, suggesting an increase in gastric tone. Have a sudden tilt down (-75°) increased (P<0.05) the PVC and CO, as well as the HR and MAP. GIT in the tilt down increased (P<0.05) gastric retention, while reducing the amplitude of gastric contractions. Both tilt up and tilt down not modify the intestinal transit liquid. Thus, passive position changes, either by sudden tilt up (+75°) or tilt down (-75°), and increases to cause hemodynamic changes the motor behavior of the gut in awake rats.